Green Growth Action Plan for Lam Dong Province for the Period of 2021 – 2030, Vision to 2050 - Mulia, R.,; Hoan, D.T.,; Pham, V.T.,; Nguyen, T.Q.,; Dewi, S.; Ekadinata, A.,; Dwiputra, A.,; Nugraha, A.,; Johana, Feri; Nguyen, K.Q.,; Nguyen, D.K.T. (World Agroforestry Centre, 2020)
The provincial Green Growth Action Plan in Viet Nam has so far focused on low-emission development, reduced greenhouse-gas emission, green production, green lifestyle, and sustainable consumption. However, there is a need for more integrated and environment-sensitive Green Growth Action Plans which can link the production, consumption, and market components of Green Growth with the safeguard of natural resources and maintenance of ecosystem services, including biodiversity, in addition to low greenhouse-gas emission. Development of such Green Growth Action Plan will be a novel initiative in Viet Nam which can ensure more sustainable economic growth within sustainable environment.